Financial Literacy and Vulnerability to Money Laundering among Young Undergraduates: A Thematic Review - Dk Nurul Jannah Bte Pg Mahari; Ieman Huda Adnan; Rusni Hassan; Hakimah Yaacob (Mandalika Institute, 2026)
Financial literacy is critical in preventing money laundering, which is a global concern that requires collaboration among regulators, law enforcement, and the general people. This paper studies young undergraduates' financial literacy levels in relation to money laundering typologies, with an emphasis on determining their vulnerability to becoming unintentional participants in financial crime. Students from Universiti Islam Sultan Sharif Ali (UNISSA) and International Islamic University Malaysia (IIUM) were interviewed using stratified random sampling to learn about money laundering activities, rules, and preventive measures. The findings show that undergraduates have inadequate financial literacy, which increases their risk of becoming involved in money laundering schemes, frequently as money mules. The report also emphasizes the importance of personal due diligence, stating that students who routinely check their financial actions are more likely to escape financial victimization. This study emphasizes the importance of targeted financial literacy programs in colleges for increasing awareness and resilience to financial crimes. The study's goal is to contribute to larger efforts to promote financial integrity and reduce the risk of exploitation in the digital age by providing kids with practical information.